The Control of Infectious Coryza in Chicken - Tati Ariyanti; Supar . (Indonesian Center for Animal Research and Development, 2007)
Infectious coryza or infectious snot is a disease caused by Haemophilus paragallinarum (HPG), that infects upper respiratory tract of either layer or broiler chickens or other poultry raised under small and large farm conditions. Infection on growing chicken caused reduction of weight gain, whereas in adult layer chicken caused decreasing egg productions, and hence significantly caused economic losses in poultry industries. Coryza cases in the farms are difficult to control by antibiotic treatments. Control by vaccination programmes using appropriate vaccines are the only ideal method, but vaccination failure using trivalent of classical serovar A, B and C of H. paragallinarum products from USA and European countries still occurred. This might probably due to the presence of new serovar B and C raised in the poultry farms in the fields, of which their antigenicity, immunogenicity and also immunoprotection of classical coryza vaccines are different from the new serovar in the fields. Research on coryza conducted at the Indonesian Research Center for Veterinary Science during the last 2 decades, resulted in some HPG isolates (belong to the classical serovar A, B or C) and these isolates were kept at the Bbalitvet Culture Collection (BCC) Unit. Studies on local isolate of HPG vaccine productions had been conducted to determine their efficacy in experimental chickens. At the same period, it was reported from Latin America and South Africa countries that new serovars B and new serovar C were found in that regions. These new serovars B and C were identified different to that of the classical serovar B or C antigenicity and immunogenicity which lead to the failure of coryza vaccination with classical serovar A, B and C imported from USA and Europe. These retrospective studies recommend that coryza is an important disease in poultry industries in this country causing a signifinant economic losses which need to be controlled properly. Further research is needed to measure the effectiveness of local isolate vaccines. Surveillance must also be conducted in order to anticipate the emerge of new HPG variant, therefore a new type of vaccine could be developed accordingly using recent local isolate. Key words: Haemophilus paragallinarum, coryza, control, vaccine